Growth Performance of Pigs as Affected by Seasonal Stress in Relation to Energy Levels in Rations - Pathak, Prasanta (Indian Journal of Animal Nutrition, 2018)
The experiment was conducted on pure-bred (Hampshire) and cross bred (50% Hampshire x 50% Local) pigs under the agro-climatic condition of Assam State, India to find out the effects of seasonal thermal stress on their growth performance. Â The experiment was also aimed to study the role of different level of energy ration (110, 100 and 90 per cent energy of NRC feeding standard for pig) in variation of growth parameters in two genetic groups of pigs in different seasons. The Metabolizable Energy value were 3260, 2936.5 and 3585.8 kcal/kg in grower ration and 3260.2, 2936.6 and 3587 kcal/kg in finisher ration for normal energy (NE), low energy (LE) and high energy (HE), respectively. The Temperature Humidity Index (THI) during the study period was found to be indicative of thermal stress to the experimental animals during summer (79.55 â€“ 82.56) as compared to the winter seasons (67.21-73.81). Higher total feed intake, daily feed intake, total gain in body weight and feed conversion efficiency (FCE) was recorded in winter season. The feed intake was comparatively higher in Hampshire but FCE was higher in Hampshire x Local. However in dietary energy wise variation, lower feed intake and higher FCE was recorded in high energy (HE) incorporated group. The average body weight was significantly (P<0.01) higher in winter and Hampshire pigs attained higher body wt. (81.80 kg). The energy level of diet had significant (P<0.01) influenced on the body weight gain and minimized the production losses in terms of body wt. gain during summer. Data indicated that in Assam, the growth performance varied with the season and during the warm season feed intake was a major limiting factor to growth rate but increasing the energy density of diet can help to minimize the effect.